BINA KOMUNIKASI, PERSEPSI BUNYI DAN IRAMA BAGI SISWA TUNARUNGU - Susilo, Budi (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2009)
Construct Communications, Sound and Rhythm Perception is to provide communication training and awareness of the sounds and rhythms to deaf students. This activity is usually conducted at a special school deaf. Construct Communications, Sound and Rhythm Perception intended for deaf students can adapt and communicate with others. Initiative and creativity of teachers is necessary in order to succeed Construct Communications, Sound and Rhythm Perception maximum and bermanafaat for students.